Pselaphinae of the Cameroon Volcanic Line. Part 3. A new genus of Goniacerini (Coleoptera: Staphylinidae: Goniaceritae) from Mount Cameroon - Hlaváč, Peter; Baňař, Petr; Fokam, Eric Bertrand (Zootaxa, 2023)
The new genus and species, Ewoma longiscapa gen. et sp. nov. of the pselaphine tribe Goniacerini based on specimens collected on Mount Cameroon are described and illustrated. The taxonomic position of the new genus within the tribe Goniacerini is discussed. The list of all genera of Goniacerini of sub-Saharan continental Africa with the number of species and the distribution as well as the list of all species known from Western Africa are given. The short overview of our knowledge of studies of the Pselaphinae of the sub-Saharan continental Africa is also provided.